Evaluation of C-Reactive Protein, Albumin and the C-Reactive Protein/ Albumin Ratio in General Surgical Trauma Patients - Ayesha Siddiqua Hashmi, Syed Ali Haider Rizvi, Asma Amin, Kiran Naz, Erum Kazim, Misbah Mahmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of in hospital mortality and to compare this frequency of mortality with CRP/Albumin ration in patients with surgical abdomen and/or chest trauma. Study Design: Cross-sectional study Place and Duration of Study: Surgical Unit IV, Civil Hospital Karachi from 26th June 2019 to 25th December 2019. Methodology: One hundred and thirty one patients with abdominal and/or chest surgical trauma were enrolled within 24 hours of trauma. Serum CRP level and serum albumin level were done through hospital hematology laboratory and CRP/albumin ration was calculated and relation with in hospital mortality was found. Results: The mean age of patients was 34.24±15.5 years with 74 male and 57 females. Mean height was 167.5±13.9 cm, mean weight was 62.6±8.6 kg and mean BMI was22.4±5.3kg/m2. Mean CRP was 14.3±9.6 mg/dl, mean albumin was 3.76±0.98 g/dl and mean CRP/Albumin ratio was 3.74±2.3.In CRP/Albumin cluster there were 32.1% patients in 0.01-2 cluster, 43.5% in 2.01-4 cluster and 32.1% in 4.01-9 cluster. 12.2% patients were expired among them there were 7.1% expiry rate in 0.01-2 cluster, 10.6% in 2.01-4 cluster and 19% patients expired in 4.01-9. Increased CRP/Albumin cluster was associated with increased mortality rate. Conclusion: An elevated CRP/Albumin ratio in traumatized patient was associated with an increased risk of mortality.